Reliability evaluation of wind turbine systemsâ components - Ahadi, Amir; Miryousefi Avval, Seyed Mohsen (Bulletin of Electrical Engineering and Informatics, 2016)
The increasing use of wind generation requests modifications in the electric power systemsplanning conception, because it includes one more uncertainty component, which needs to bestudied properly and modeled. Understanding the failures rates and downtimes of wind turbinesis dicult not only because of the considerable range of designs and sizes that are now in serviceworldwide but also since studies are conducted independently under various operating conditionsin dierent countries. The fault tree method (FTA) has been used to study the reliability of manydierent power generation systems. This paper now applies that method to a wind turbine systemto estimate the reliability of wind turbines. In the implementations, several types of wind turbineswere considered in order to analyze the systemâs reliability. The eectiveness of the proposedmethod is revealed through several case studies.